El Col·lectari-Ordinari de l'Abadia de Santa Maria de la Grassa (París, BnF, ms. lat. 933) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2008)
The manuscript Paris, BnF, lat 933 is a monastic Collectary-Ordinary from the abbey of Lagrasse nearby Carcassonne. The oldest part of the manuscript is dated around 1075-1100 and seems to have been written at the same abbey. The Collectary is related to the mixed Gregorian Sacramentary used in the Narbonnese, while the Ordinary follows the Catalan-Narbonnese tradition. In the second quarter of the 12th century, in times of Abbot Berenguer, step-brother of Count Ramon Berenguer III of Barcelona, the original Ordinary was completed with a large supplement and later, in the first half of the 13th century, the Collectary was completed for update by another supplement of clear Provençal, precisely Saintvictorian influence. This manuscript is crucial to know the liturgical usage at Narbonnese monasteries in Languedoc.